Presence of pleomorphic features but not growth patterns improves prognostic stratification of epithelioid malignant pleural mesothelioma by 2‐tier nuclear grade. Issue 3 (29th June 2020) - Zhang, Yu Z; Brambilla, Cecilia; Molyneaux, Philip L; Rice, Alexandra; Robertus, Jan L; Jordan, Simon; Lim, Eric; Lang‐Lazdunski, Loic; Begum, Sofina; Dusmet, Michael; Anikin, Vladimir; Beddow, Emma; et al.
Abstract: Aims: Nuclear grade has been recently validated as a powerful prognostic tool in epithelioid malignant pleural mesothelioma (E‐MPM). In other studies histological parameters including pleomorphic features and growth patterns were also shown to exert prognostic impact. The primary aims of our study are (i) externally validate the prognostic role of pleomorphic features in E‐MPM and (ii) investigate if evaluating growth pattern in addition to 2‐tier nuclear grade improves prognostication. Methods and results: 614 consecutive cases of E‐MPM from our institution over a period of 15 years were retrospectively reviewed, of which 51 showed pleomorphic features. E‐MPM with pleomorphic features showed significantly worse overall survival compared to those without (5.4 versus 14.7 months). Tumours with predominantly micropapillary pattern showed the worst survival (6.2 months) followed by solid (10.5 months), microcystic (15.3 months), discohesive (16.1 months), trabecular (17.6 months) and tubulo‐papillary (18.6 months). Sub‐classification of growth patterns into high grade (solid, micropapillary) and low grade (all others) led to good separation of overall survival (10.5 versus 18.0 months) but did not predict survival independent of 2‐tier nuclear grade. A composite score comprised of growth pattern and 2‐tier nuclear grade did not improve prognostication compared with nuclear grade alone. Intra‐tumoural heterogeneity in growth patterns is ubiquitous. Conclusions: Our findings support the incorporation of E‐MPM with pleomorphic features in the epithelioid subtype as a highly aggressive variant distinct from 2‐tier nuclear grade. E‐MPM demonstrates extensive heterogeneity in growth pattern but its evaluation does not offer additional prognostic utility to 2‐tier nuclear grade.